PENGARUH SIKAP KEUANGAN, PERILAKU KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN UMKM PADA PEMDES AMBENGAN - Nopiyani, Putu Eka; Indiani, Putu Rara (Komunitas Manajemen Kompetitif, 2023)
This study aims to determine the effect of financial attitudes, financial behavior and financial literacy on the financial performance of MSMEs in Pemdes Ambengan. The population taken is the number of MSME actors in the Ambengan Village Government in 2022 as many as 532 and a sample of 85 people calculated using the slovin formula. The data analysis technique used in this study is Multiple Linear Regression Analysis, Classical Assumption Test, Model Feasibility Test (Goodness Of Fit), Hypothesis Test using the SPSS Version 21.0 application for windows. The results of this study indicate that the influence of financial attitudes has a positive and significant effect on the financial performance of the UMKM Pemdes Ambengan. Financial behavior has a positive and significant effect on the financial performance of the UMKM Pemdes Ambengan. Financial literacy has a positive and significant effect on the financial performance of the UMKM Pemdes Ambengan.